(untitled) (Research, Society and Development, 2022)
This article is part of the discussions on the concept of Pedagogical Work and derives from a study that aimed to analyze the academic production on pedagogical work, from 2011 to 2021, available in the Repository of Theses and Dissertations of a Federal University in the country of the State of Rio Grande do Sul. From a bibliographical research and document analysis, 18 dissertations and 11 theses were studied. Above all, the approach of the Pedagogical Work category/concept was analyzed. With this, it was possible to observe that all studies departed from Ferreira’s conception (2010 to 2018) and, in different contexts and themes, applied the category to different school or training spaces. Furthermore, it was possible to observe divergences and, in the same way, punctual convergences between the studies that point to the need for more studies and development of the concept, which, in short, aims to explain the work of teachers.